(untitled) (LEARNing Landscapes, 2020)
We examine the benefits of developing critically reflexive learners through life story performance embedded in a Critical Reflexive Model. Students are invited to work with their life stories in a safe, dialogical space and to deconstruct various forms of power and its influence on their lives. Using a mix of creative and embodied methodologies, students explore their values, agency, and performativity to enable a deeper level of critical reflexivity. As researchers, we track what ongoing contributions reflexivity has made to the lives of students after graduating and currently working in the field as professionals. Our findings indicate that students experience shifts in their perception of self, others, and their contexts, which make them better placed to respond to the many complexities of society in South Africa on both a personal and a professional level.